Obstetric Skills Competency Curriculum for Residency Preparation. (October 2017) - Marko, Emily; Downing, David; Buery-Joyner, Samantha; McLeod, Francine; Nieves, Kelsey
Abstract : BACKGROUND: A joint task force designed resident competency milestones from levels 1 to 5. Medical students entering residency will need to be competent at level 1 and progress through level 2 during internship. METHODS: A curriculum of nine obstetric skills modules for level 1 and 2 milestones was evaluated over a 3-year period. Instructional methods included team-based learning and skills workshops using low-fidelity simulated models. Assessment was performed using objective structured clinical exam. Forty-eight medical students from two campuses were given pre-/posttests, competency assessments, and confidence surveys. Follow-up surveys were collected after starting residencies. RESULTS: All students achieved level one competency by the end of the program. Test scores were significantly improved for each module, with the greatest improvements noted in obstetric emergencies (+56.54, P =.0001), spontaneous vaginal delivery (+42.65%, P =.0001), perineal lacerations (+34.50, P =.000), obstetric ultrasonography (+34.40%, P =.0001), and cervical assessment (+33.33%, P =.0001). Student confidence levels showed greatest improvements in obstetric emergencies (+63.14, P =.0001), perineal lacerations (+53.80%, P =.0001), and surgical principles (+46.20%, P =.0001). Follow-up surveys (1=high, 5=low) indicated that the program prepared them well in knowledge (1.73), surgical skills (2.0), obstetric skills (1.53), patient assessment (2.13), and patient management (2.4). Moreover, 86.67% of participants felt more prepared for residency than their fellow interns. DISCUSSION: This simulation-based curriculum for obstetric skills was effective at improving the knowledge, skills and attitudes of medical students matched into obstetric residencies. This program offers tools for milestone competencies and effectively prepared interns for day 1.